Technology and knowledge flow : the power of networks - Trentin, Guglielmo (Chandos information professional series., 2011)
This book outlines how network technology can support, foster and enhance the Knowledge Management, Sharing and Development (KMSD) processes in professional environments through the activation of both formal and informal knowledge flows. Understanding how ICT can be made available to such flows in the knowledge society is a factor that cannot be disregarded and is confirmed by the increasing interest of companies in new forms of software-mediated social interaction. The latter factor is in relation both to the possibility of accelerating internal communication and problem solving processes, and/or in relation to dynamics of endogenous knowledge growth of human resources. The book will focus specifically on knowledge flow (KF) processes occurring within networked communities of professionals (NCP) and the associated virtual community environments (VCE) that foster horizontal dynamics in the management, sharing and development of fresh knowledge. Along this line a further key issue will concern the analysis and evaluation techniques of the impact of Network Technology use on both community KF and NCP performance. The proposal of a taxonomy of Network Technology uses to support formal and informal knowledge flowsAnalyses how Web 2.0 and Web 3.0 technology is deeply modifying the dynamics connected to KF and KMDiscusses dynamics underlying horizontal KF sharing processes within NCP.